Optimizing Management to Reduce the Mortality of COVID-19: Experience From a Designated Hospital for Severely and Critically Ill Patients in China - Zhu, Wei; Zhang, Huaqiu; Li, Yong; Ding, Zeyang; Liu, Zhuo; Ruan, Yajun; Feng, Huan; Li, Ganxun; Liu, Bo; He, Fan; Zhou, Ning; Jiang, Jiangang; et al. (Frontiers in Medicine, 2021)
Abstract In this retrospective, single-center study, we included 1106 COVID-19 patients in Optical Valley Branch of Tongji Hospital from February 9 to March 9, 2020. Cases were analyzed for demographic, clinical features, laboratory data, and treatment method. Inflammation-related indices (hs-CRP, ESR, serum ferritin, and procalcitonin) were significantly higher in severe and critically ill patients than those in moderate patients. Cytokines including IL-6, IL2R, IL-8, TNF-α were also higher in severe and critically ill patients. Acute respiratory distress syndrome (ARDS) occurred in 23.0% (99/431) severe and critically ill patients. Sixty-one patients were treated by invasive mechanical ventilation, the correlation between SpO2/FiO2 and PaO2/FiO2 was confirmed, and the cut-off value of SpO2/FiO2 related to survival was 134.43. The mortality of patients with low SpO2/FiO2(<134.43) of intubation was higher than that of patients with high SpO2/FiO2(>134.43) (72.7% vs. 33.3%). In intubation patients the use rate of glucocorticoid therapy, CRRT, and anticoagulation treatment was 77.0% (47/61), 54.1% (33/61), and 98.4% (60/61). Comprehensive treatment including ventilatory support, multiple organ function preservation, glucocorticoid usage, renal replacement therapy, anticoagulation, restrictive fluid management, and nutrition improvement was the main method. Early recognition and intervention, multidisciplinary collaboration, and personalized treatment might be the core strategies in reducing mortality.